The stent for life initiative in Portugal: A critical realist perspective - Major, M.; Martins, L. (International Journal of Healthcare Technology and Management, 2023)
Drawing on the morphogenetic approach proposed by Archer (1995), this study explains how the stent for life (SFL) initiative emerged and developed in Portugal and how it was embraced as a means to reduce mortality following acute myocardial infarction. A qualitative research strategy based upon a case study was adopted. Only by conducting qualitative research was it possible to interact context with explanation and produce understandings for the 'who', 'when', 'why', 'how' and 'what' of SFL in Portugal (Mason, 2018; Ackroyd and Karlsson, 2014; Yin, 2015). Archer's morphogenetic approach makes analytical dualism explicit and therefore very useful in accounting for the existence of prior material structures and cultural structures that affected (but did not determine) agents' actions. The investigation revealed that there was morphogenesis (i.e., the former structures were transformed) and that new structures emerged from the intended consequences of agents' activities.